Transfusion medicine and hemostasis : clinical and laboratory aspects - Hillyer, Christopher D.; Shaz, Beth H.; Zimring, James C.; Abshire, Thomas C. (Amsterdam : Elsevier, 2009)
Transfusion Medicine and Hemostasis is a manual-style book that links transfusion medicine and hemostasis to laboratory methods and diagnostic tests engaged in routine and specialized coagulation laboratories. The book is divided into two main parts with chapters that are brief and readable. The first main part of the book is subdivided into blood banking and transfusion medicine. Under blood banking, the chapters cover blood collection, donation process, component manufacturing, donor testing and storage; transfusion-medicine chapters examine the components for transfusion, pre-transfusion immunohematology testing, blood groups, blood products and their modifications, approaches to transfusion therapy in specific clinical settings, and transfusion reactions and complications. In addition, chapters that talk about apheresis, cellular therapy, and tissue banking in the hospital setting are included. Hemostasis, the second main part of the book, is subdivided into three sections. The first section, clinical coagulation, includes chapters about neonatal thrombocytopenia, inherited platelet function disorders, immune thrombocytopenia, immune-mediated coagulopathies, congenital bleeding disorders, and acquired bleeding disorders. The second section relates to laboratory testing of coagulation, with chapters about laboratory assessments of platelet disorders, von Willebrand disease, coagulation factor disorders, fibrinogen and fibrinolysis, tests for hypercoagulable state and for activation of the coagulation system, and laboratory support for anticoagulation. The third section discusses coagulation factor products. This book will be valuable for the education of trainees, practitioners, and future leaders in these fields.
Hrebeňová väzba
Obsahuje biografické údaje o autoroch
Obsahuje bibliografiu, bibliografické odkazy a register
Keywords: lekárstvo transfúzne; hematológia; javy fyziologické krvné; prípravky hematologické; darcovstvo krvi; banky krvné; hemostáza; choroby hematologické; techniky klinické laboratórne; testy hematologické; testy hemokoagulačné; monografia